Designing an Information System for Inventory Forecasting: (Case Study: Samsung Partner Plaza, Sorong City) - Matheus Rumetna; Elisabeth Esmeralda Renny; Tirsa Ninia Lina (Indonesian Scientific Journal, 2020)
Samsung Partner Plaza is a company that sells smartphones and serves large-scale sales by adopting the membership and computerized systems. The company’s inventory management activities consist of the normal inventory flow direction and management, ranging from the inventory procurement, storage to sales. The company would often face a problem where it would be running out of finished goods inventory to be sold in coming months. The remaining inventory would be inadequate to meet the customer demands. Such situation, and the fact that the company has competitors both inside and outside Sorong city, might cause customers to find other companies that could meet their demands, thus reducing the company’s capacity to generate profit. Given the situation, this research was conducted to create an information system which could be used by Samsung Partner Plaza for inventory forecasting. The system would provide information regarding the correct amount of inventory which could meet the customer demands. The waterfall method was employed to develop the system whereas the exponential smoothing method was employed by the system to perform forecasting. The research produced a forecasting information system which was helpful for the company in predicting the adequate amount of inventory to be ordered to meet the customer demands. The system was tested using the Black Box testing and the results showed that all functions of the system worked well (valid).